Nitrogen fixation by the diazotroph Cylindrospermopsis raciborskii (Cyanophyceae). Issue 5 (18th October 2016) - Willis, Anusuya; Chuang, Ann W.; Burford, Michele A.
Abstract : Nitrogen fixation has been proposed as a mechanism that allows the diazotrophic cyanobacterium, Cylindrospermopsis raciborskii, to bloom in nitrogen‐limited freshwater systems. However, it is unclear whether dinitrogen fixation (N2 fixation) can supplement available dissolved inorganic nitrogen (DIN) for growth, or only provides minimum nitrogen (N) for cell maintenance under DIN deplete conditions. Additionally, the rate at which cells can switch between DIN use and N2 fixation is unknown. This study investigated N2 fixation under a range of nitrate concentrations. Cultures were grown with pretreatments of nitrate replete (single dose 941 μmol NO 3 −  · L −1 ) and N‐free conditions and then either received a single dose of 941 μmol NO 3 −  · L −1 (N941), 118 μmol NO 3 −  · L −1 (N118) or 0 N. Heterocysts appeared from days 3 to 5 when treatments of high NO 3 − were transferred to N free media (N941:N0), and from day 5 in N941 transferred to N118 treatments. Conversely, transferring cells from N0 to N941 resulted in heterocysts being discarded from day 3 and day 5 for N0:N118. Heterocyst appearance correlated with a detectable rate of N2 fixation and up‐regulation of nifH gene expression, the discard of heterocysts occurred after sequential reduction of nifH expression and N2 fixation. Nitrate uptake rates were not affected by pretreatment, suggesting no regulation or saturation of this uptake pathway. These data demonstrate that for C. raciborskii, N2 fixation is regulated by the production or discard of heterocysts. In conclusion, this study has shown that N2 fixation only provides enough N to support relatively low growth under N‐limited conditions, and does not supplement available nitrate to increase growth rates.